Adrenal response of male rats exposed to prenatal stress and early postnatal stimulation. (August 2015) - Liaudat, AC; Rodríguez, N; Chen, S; Romanini, MC; Vivas, A; Rolando, A; Gauna, H; Mayer, N
Abstract Stress in pregnant rats caused by chronic immobilization alters the pattern of secretion of corticosterone and modifies the hypothalamic-pituitary-adrenal axis (HPA) of the fetus. Early postnatal handling, however, may reverse the effects of increased secretion of corticosterone. We investigated the effects of prenatal stress and postnatal handling on the activity of the HPA axis of male offspring of stressed female rats. Male 90-day-old rats from four groups were investigated: prenatally stressed animals without postnatal handling, prenatally stressed animals with postnatal handling, unstressed control animals with postnatal handling, and unstressed control animals without postnatal handling. After sacrifice, the adrenal glands were weighed to determine the adrenal-somatic index. Apoptosis was evaluated by TUNEL assay and active caspase-3 expression. We found that the adrenal gland cortex:medulla ratio increased in animals with prenatal stress and that eventually the stress caused apoptosis. Handling newborns to simulate maternal activity ameliorated some of the negative effects of prenatal stress.